Climate change and human footprint increase insect defoliation across central boreal forests of Canada - Kalamandeen, Michelle; Gulamhussein, Imran; Castro, Jose Bermudez; Sothe, Camile; Rogers, Cheryl A.; Snider, James; Gonsamo, Alemu (Frontiers in Ecology and Evolution, 2023)
Anthropogenic climate change is contributing to increased insect infestation globally, leading to pest population growth, expansion of niche and geographic ranges as well as increased outbreak frequencies, resulting in economic losses and reduction in food security. In recent years, Spongy Moth (Lymantria dispar dispar ), Jack Pine Budworm (Choristoneura pinus pinus), Large Aspen Tortrix (Choristoneura conflictana) and Spruce Budworm (Choristoneura fumiferana) caused widespread defoliation across one of Canada's most forested provinces, Ontario. Observations of such outbreaks have been limited to field sightings around Ontario, with few studies focused on mapping of outbreak occurrence across the province or exploring potential anthropogenic and climatic drivers of infestation. Using random forest probability estimates and satellite data resampled to 1 km spatial resolution from the Moderate Resolution Imaging Spectroradiometer (MODIS), we reveal greater expansion of insect defoliation across Ontario between 2018 and 2020 than previously recorded. Much of the geographic expansion of outbreaks was driven by increasing temperature, and the proximity of roads. With ongoing global warming and growing economic development, infestations will not only continue to increase across Ontario but also expand northward due to their responses to accelerated warming at higher latitudes. This expansion presents an important and alarming new challenge for forest conservation and management in Ontario, in particular, and Canada in general.